Guidelines for the safe provision of anaesthesia in magnetic resonance units 2019: Guidelines from the Association of Anaesthetists and the Neuro Anaesthesia and Critical Care Society of Great Britain and Ireland. (3rd February 2019) - Wilson, S. R.; Shinde, S.; Appleby, I.; Boscoe, M.; Conway, D.; Dryden, C.; Ferguson, K.; Gedroyc, W.; Kinsella, S. M.; Nathanson, M. H.; Thorne, J.; White, M.; et al.
Summary: There has been an increase in the number of units providing anaesthesia for magnetic resonance imaging and the strength of magnetic resonance scanners, as well as the number of interventions and operations performed within the magnetic resonance environment. More devices and implants are now magnetic resonance imaging conditional, allowing scans to be undertaken in patients for whom this was previously not possible. There has also been a revision in terminology relating to magnetic resonance safety of devices. These guidelines have been put together by organisations who are involved in the pathways for patients needing magnetic resonance imaging. They reinforce the safety aspects of providing anaesthesia in the magnetic resonance environment, from the multidisciplinary decision making process, the seniority of anaesthetist accompanying the patient, to training in the recognition of hazards of anaesthesia in the magnetic resonance environment. For many anaesthetists this is an unfamiliar site to give anaesthesia, often in a remote site. Hospitals should develop and audit governance procedures to ensure that anaesthetists of all grades are competent to deliver anaesthesia safely in this area.